Firecracker-induced gastric perforation: A case report and review of literature - Singh, Amandeep; Kaur, Haramritpal; Singh, Sonam; Kaur, Ramanjeet; Karthick, A (Indian Journal of Case Reports, 2020)
Firecracker-induced injuries are commonly reported as superficial soft-tissue injuries affecting the head, neck, and upper limbs. Deep penetrating injuries due to firecrackers misuse are a less known identity. People usually suffer from firecracker injuries due to misuse or because of their risk-taking behavior. Such cases pose a special challenge to the surgeons due to the type of population, usually young and the social, cultural, legal, and emotional factors involved with the injuries. Judicious decisions and empathy toward patients as well as toward relatives can resolve lots of problems. We are hereby reporting a rare case of gastric perforation in a young 22-year-old male which was caused by a broken piece of steel glass due to the explosion of a firecracker.